LiMg(IO 3 ) 3 : an excellent SHG material designed by single-site aliovalent substitution - Chen, Jin; Hu, Chun-Li; Mao, Fei-Fei; Zhang, Xiao-Han; Yang, Bing-Ping; Mao, Jiang-Gao (Chemical science (Cambridge), 2019)
An excellent second harmonic generation (SHG) material, LiMg(IO 3 ) 3 (LMIO), has been elaborately designed from Li 2 M IV (IO 3 ) 6 (M IV = Ti, Sn, and Ge) by aliovalent substitution of the central M IV cation followed by Wyckoff position exchange. The new structure sustains the ideal-alignment of (IO 3 ) − groups. Importantly, LMIO exhibits an extremely strong SHG effect of roughly 24 × KH 2 PO 4 (KDP) under 1064 nm laser radiation or 1.5 × AgGaS 2 (AGS) under 2.05 μm laser radiation, which is larger than that of α-LiIO 3 (18 × KDP). The replacement of M IV with Mg 2+ without d–d electronic transitions induces an obviously larger band gap (4.34 eV) with a short absorption edge (285 nm). This study shows that single-site aliovalent substitution provides a new synthetic route for designing SHG materials.